ANALYSIS AND IMPLEMENTATION OF THE INTERNET OF THINGS (IoT) IN THE DEVELOPMENT OF MONITORING SOLAR POWER PLANTS (PLTS) 600 WP - Abdulghani, Tarmin; Nazilah, Siti; Legiawan, M. Kany; Sulaeman, Fietri Setiawati; Setiadi, Moch Fahmi (Jurnal Teknik Informatika (Jutif), 2024)
Solar power plants are becoming an increasingly popular solution for providing clean and sustainable energy. However, careful monitoring is required to maximize their performance, and it is necessary to monitor the functioning of solar power plants devices. This study proposes developing an Internet of Things (IoT)-based monitoring system for solar power plants using the PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) method. The Prepare stage involves identifying monitoring needs, while the Plan stage includes infrastructure planning and sensor selection. The Design stage focuses on the design of a monitoring system that suits the needs of PLTS. The implementation stage involves the installation and configuration of hardware and software. Afterward, the Operate stage ensures that the system is running properly, while the Optimize stage aims to improve the system's performance continuously. Through this approach, we strive to present a systematic and structured framework for developing solar farms with IoT monitoring systems.